Integrating CSR into value chain management in developing countries: A study in Chinese leather industry - Jiang, Huan (2020)
This research investigates the linkage between Corporate Social Responsibilities (CSR) and Value Chain Management (VCM), which further suggests CSR value and how companies achieve these values in VCM. CSR defined by Sternberg (1997) implies a business commitment to sustainable markets with not only economic growth but also ecological and social considerations. Approaches of integrating economic, social and ecological responsibilities into downstream and upstream in chains mainly focus on strategy and recourse management (Cruz and Boehe 2008). According to Porter's (1985) strategy management, companies can gain competitiveness from not only differentiation aiming at differentiated CSR products with different marketing strategies but also cost and efficiency management in integrated activities. Besides, Schavana et al. (2019) propose the capital flow to increase the capabilities of value chains in aspects of human and environmental capital. The value created through value chains in practice consists of financial benefits (e.g. better financial performance, more efficiency of global trading, higher quality, lean production, and core value) and social and environmental benefits including low emissions, less energy consumption, awareness-raising, trusted relationships with stakeholders, and improving social welfare (Africa et al., 2014 and Calabrese et al., 2013). However, problems of increasing investments, coherence of integrity, compliance risks, and information quality have been identified in practice. Future researches should analyze the effectiveness of CSR disclosures and the priority of drivers of CSR and VCM that emphasize economic considerations in this research showing the impacts of market, regulation, management efficiency as well as relationship management, which implies growth of value creation.